(untitled) (Journal of Asian Development Studies, 2024)
The purpose of this study is to identify and validate the antecedents and outcomes of environmental sustainability in green manufacturing in Pakistan, by principally focusing on small and mediumsized enterprises (SMEs). This study examines the role of knowledge management processes (KMPs), specifically the knowledge acquisition, knowledge dissemination, and knowledge application, as enablers of environmental sustainability. Data were collected from 487 SMEs through an online survey and analyzed using partial least squares structural equation modeling (PLS-SEM). This study investigates the relationship between innovation, knowledge management, and environmental sustainability in the context of green manufacturing. Significant findings indicate that: (1) innovation has a significant impact on environmental sustainability and (2) knowledge management moderates the relationship between innovation and environmental sustainability. The contributions of this study to the existing literature include: (1) providing a comprehensive framework linking environmental sustainability enablers to innovation in green manufacturing sector and (2) establishing knowledge management as a mediator between innovation and environmental sustainability. The findings of this study have important implications for policymakers, managers, and researchers in understanding the dynamics of environmental sustainability in SMEs of green manufacturing in Pakistan. This study also discusses future research directions and limitations